2016
DOI: 10.3109/0886022x.2016.1172917
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of leflunomide combined with prednisone in the treatment of refractory nephrotic syndrome

Abstract: Objective: To assess the safety and clinical efficacy of leflunomide (LEF) and prednisone on refractory nephrotic syndrome (RNS). Methods: A total of 52 patients with RNS were treated for 24 weeks between 2010 and 2014 in our hospital. In the treated group, 26 patients were treated with LEF and prednisone, and, in the control group, 26 patients were treated with cyclophosphamide (CTX) and prednisone. During the treatment, 24 h urinary protein excretion and the serum levels of albumin and cholesterol, and kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…reported leflunomide could improve renal injury of DN rats through its inhibition of OPN/TGF-β1 mediated extracellular matrix deposition and tubulointerstitial fibrosis [18]. Another recent study also demonstrated that the combined use of leflunomide and prednisone had good efficiency in treatment of refractory nephrotic syndrome [19]. In the present study, we also showed leflunomide could improve the renal function and reduce the renal injury of DN rats, which was in consistent of other researches.…”
Section: Discussionsupporting
confidence: 90%
“…reported leflunomide could improve renal injury of DN rats through its inhibition of OPN/TGF-β1 mediated extracellular matrix deposition and tubulointerstitial fibrosis [18]. Another recent study also demonstrated that the combined use of leflunomide and prednisone had good efficiency in treatment of refractory nephrotic syndrome [19]. In the present study, we also showed leflunomide could improve the renal function and reduce the renal injury of DN rats, which was in consistent of other researches.…”
Section: Discussionsupporting
confidence: 90%
“…For patients with PMN, the use of cyclophosphamide varies from center to center. Previously, our center reported a CTX dose of 8-12 mg/kg/per administration, given once every four weeks [40]. However, a large number of clinical observations suggest slow improvements in edema and proteinuria.…”
Section: Discussionmentioning
confidence: 99%